Examining the Moderating Effects of Students’ Characteristics on the Relationship between Perceived Quality and Satisfaction with University Services: The Evidence from two Public Universities in Terengganu - Padlee, Siti Falindah; Zulkiffli, Siti Nur â€˜Atikah (International Review of Management and Marketing, 2016)
The success of economic development in ECER is contributed by many factors such as investment from foreign countries, tourism industry, oil and gas industry as well as education industry. With regards to education industry, the number of higher educational institutions in ECER has increased. To achieve the mission of ECER in strengthening the education system and as an educational hub, it is of utmost importance, especially for universities in Terengganu to identify strategies in achieving the mission. The research to identify and understand the students’ characteristics is important for marketers to attract and retain students especially for HEIs in ECER. Thus, the objectives of this research is to (1) assess the relationship between perceived quality and overall satisfaction and (2) test the moderating effects of students’ characteristics’ such as gender, race and state of origin on the relationship between perceived quality and satisfaction with university services. The regression analysis was used to analyze the hypotheses of the study and the results supported both hypotheses. For the first hypothesis, there was a significant positive relationship between perceived quality and satisfaction. For the second hypothesis, the moderating effects of students’ characteristics supported the relationship between overall satisfaction and behavioural intentions. The analysis revealed that students’ characteristics had significant impact as a moderator. Keywords: ECER, Education industry, Service Quality, Satisfaction, Regression Analysis JEL Classification: M3